2017
DOI: 10.1177/0263775817709018
|View full text |Cite
|
Sign up to set email alerts
|

#HotForBots: Sex, the non-human and digitally mediated spaces of intimate encounter

Abstract: Contemporary practices of sex and intimacy are increasingly digitally mediated. In this paper, we identify two distinctly spatial effects of these mediations. First, the digital extends the spaces of sex/uality beyond the immediately proximate, simultaneously expanding the potential for non-human object choice in intimate encounters. Second, the digital intensifies the experiential fidelity of intimate encounters by folding the remote into the spatially immediate, such that non-proximate intimate relations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…That motivation is writ large in the emphasis of these platforms on embodied, rather than only virtual, encounter. Indeed, the almost‐immediate gratifications offered by these locative media represent one key way in which digitally mediated sex and sexualities comprise new “spaces of encounter” (Cockayne, Leszczynski, & Zook, , p. 1128). Far from a wholesale move to online life as predicted in the early days of the internet, locative networks pivot more , rather than less, on physically brokered connection.…”
Section: Queer Locative Mediamentioning
confidence: 99%
“…That motivation is writ large in the emphasis of these platforms on embodied, rather than only virtual, encounter. Indeed, the almost‐immediate gratifications offered by these locative media represent one key way in which digitally mediated sex and sexualities comprise new “spaces of encounter” (Cockayne, Leszczynski, & Zook, , p. 1128). Far from a wholesale move to online life as predicted in the early days of the internet, locative networks pivot more , rather than less, on physically brokered connection.…”
Section: Queer Locative Mediamentioning
confidence: 99%
“…Contact brokered online sometimes stays in the virtual world (McGlotten, 2013;Miles, 2019), particularly in places where local culture makes meeting in public difficult -such as in parts of the Middle East where men and women cannot easily mix (Costa and Menin, 2016;Kaya, 2009) or for those with limited physical mobility, where online fora may offer a social lifeline (Dobransky and Hargittai, 2006). Digital technology can not only extend possibilities for stranger intimacy beyond the immediately proximate, it can also intensify these encounters by transmitting audio, images or video that make them feel more proximate (Cockayne et al, 2017).…”
Section: Researching Stranger Intimacymentioning
confidence: 99%
“…Thinking more widely, digitally mediated forms of stranger intimacy or avoidance can be situated within a wider process of boundaryblurring in our contemporary moment taking place between conventional relations of public/private (Koch, 2020;Qian, 2018), and by association between relations such as formal/ informal work (Glucksmann, 2011;Wheeler and Glucksmann, 2014), between producers/ consumers (Bruns, 2010;Ritzler and Jurgenson, 2010) and in terms of social categories such as friend, guest, host or community member. Further, Cockayne et al (2017) have demonstrated that digital technology can also extend intimacy to the non-or more-thanhuman as people knowingly interact, for example, with robots and algorithms designed to simulate human dialogue in the pursuit of sexual pleasure and fantasy. This parallels work on the role that objects such as the car can play in constituting new forms of relations among unknown others where intimate acts of sharing, caring and even co-ownership emerge (Dowling et al, 2018).…”
Section: Researching Stranger Intimacymentioning
confidence: 99%
“…But regardless of its ethical valence, scholars have consistently theorised the encounter in relation to particular places and usually emphasise the geographical proximity of individuals (though see Cockayne et al. [] who discuss remote digital encounters and Wilson , who discusses remote textual and aesthetic encounters with cityscapes). Encounter has been taken to be inherently spatial but the spatiality of the encounter itself – what we'll discuss here in terms of its topological unfolding – has received much less attention.…”
Section: Engaging Space and Difference Through The Encountermentioning
confidence: 99%
“…Indeed, many geographers have examined how difference and space could be considered co‐extensive or mutually constituted, and the idea of space‐as‐difference reverberates across geographic scholarship (Cockayne et al., ; Doel, ; Jacobs & Fincher, ; Massey, ; McDowell, ; Valentine, ). Moving beyond utopian conceptualisations of the encounter as necessarily generative of positive understandings of difference (Valentine, ) – a notion often underwritten by the assumptions of liberal and representational cosmopolitan politics – geographers continue to see the encounter as a way to think through what happens at meeting points and contact zones, whether they be in physical or in digital spaces (Askins & Pain, ; Cockayne et al., ). Yet arguably, the encounter remains undertheorised, leaving open a series of questions around precisely how key terms like space, difference, and embodiment could be conceptualised (Wilson, ; Wilson & Darling, ).…”
Section: Introduction: Encountering Space and Differencementioning
confidence: 99%